2005
DOI: 10.1089/ten.2005.11.1122
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties and Remodeling of Hybrid Cardiac Constructs Made from Heart Cells, Fibrin, and Biodegradable, Elastomeric Knitted Fabric

Abstract: Hybrid cardiac constructs with mechanical properties suitable for in vitro loading studies and in vivo implantation were constructed from neonatal rat heart cells, fibrin (Fn), and biodegradable knitted fabric (Knit). Initial (2-h) constructs were compared with native heart tissue, studied in vitro with respect to mechanical function (stiffness, ultimate tensile strength [UTS], failure strain epsilon(f), strain energy density E) and compositional remodeling (collagen, DNA), and implanted in vivo. For 2-h const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
87
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(89 citation statements)
references
References 38 publications
1
87
1
Order By: Relevance
“…4). The breaking strain was comparable to that of the rat heart (about 75%) and the tensile strength was close to or higher than that of the rat heart (approximately 40 kPa) (41). The general similarities in these tensile properties to that of the rat heart would be attractive in cardiac wall tissue engineering.…”
Section: Discussionmentioning
confidence: 68%
“…4). The breaking strain was comparable to that of the rat heart (about 75%) and the tensile strength was close to or higher than that of the rat heart (approximately 40 kPa) (41). The general similarities in these tensile properties to that of the rat heart would be attractive in cardiac wall tissue engineering.…”
Section: Discussionmentioning
confidence: 68%
“…The breaking strain was comparable to that of the rat heart (approximately 75%) while the tensile strength was six-fold higher than the rat heart (approximately 0.04 MPa). [45] The difference in mechanical properties for the tubular and cylindrical scaffolds can be attributed to differences in the surface structure. The tubular scaffolds had outer and inner surfaces with small pores (Figure 1c).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with native cardiac heart tissue, the composites had mechanical properties that were stiffer than native heart muscle, which is made of collagen and is elastomeric with a stiffness of approximately 50-100 kPa during diastole. [26][27][28][29] However, the modulus of active myocardium during systole is approximately 20-fold higher, 30,31 so more closely resembles that of PLGA:CNF composites. These results indicated that the addition of CNF increased the composite tensile strength to mirror better the ability to strengthen the myocardium.…”
Section: Tensile Testsmentioning
confidence: 97%